Estimation of Crop Water and Irrigation Requirement for Major Cereals and Vegetable Crops Using FAO CROPWAT 8.0 Model in the Terai Region of Nepal - Adhikari, Tikaram; Bhusal, Anita; Bhatta, Rasmita; Chaudhary Dhami, Manila Singh; Hamal, Samikshya (Far Western Review, 2025)
To optimize food production and meet the needs of the ever-increasing population, there is a need to utilize agricultural water economically and scientifically. There are barely enough scientific studies done on agricultural water requirements in Nepal resulting in a lack of information available to Nepalese farmers regarding agricultural water management. This study utilizes the CROPWAT 8.0 model to estimate the Crop Water Requirement (CWR) and Irrigation Requirement (IR) for key crops, including rice, maize, wheat, potato, and cauliflower, in Nepal's Terai region. Agro-climatic data, encompassing rainfall, maximum and minimum temperatures, sunlight hours, humidity, and wind, were sourced from the NASA power tool. Crop data were obtained from FAO statistics, and soil data were derived from the Nepal Agricultural Research Council (NARC) soil map. The study revealed significant variations in CWR, ranging from 321.70 mm for potatoes in Dang to 1009.10 mm for paddy in Kailali, and IR, ranging from 86.80 mm for maize in Morang to 802.30 mm for paddy in Kailali. This research study indicates that the seasonal and ecological features of the location necessitate crop water requirements and irrigation schedules that are specific to them. The knowledge on crop water demand help farmers to determine the optimal timing and quantity of irrigation for various crops, thereby mitigating water wastage. These findings offer valuable insights for farmers and researchers to enhance irrigation water management practices in agricultural contexts, promoting sustainable water management.